Effects of Adding Fennel (Foeniculum vulgare) In Rations on Fattening Performance and Blood Oxidant-Antioxidant Balance in Rams - Sibel ALAPALA; Yasemin SUNUCU KARAFAKIOĞLU; Salih SEZER; Funda KARABAĞ (ISPEC Journal of Agricultural Sciences, 2024)
This study aimed to determine the effects of adding fennel seeds (Foeniculum vulgare) to the diet on the biochemical parameters and live weight gains in rams. Thirty male rams of the Eşme breed, with an average live weight of 39 kg, were used, divided into two groups, each containing 15 rams. The control group received a ration without any additional supplementation, while the treatment group had fennel seeds added to their rations at a rate of 1.5 % per animal per day for 60 days. At the end of the experiment, blood samples were collected from the sheep to analyze malondialdehyde (MDA), protein carbonyl concentrations (PCO), superoxide dismutase (SOD), and catalase (CAT) enzyme activities. The study found a statistically significant difference between the groups in terms of daily live weight gain, with the control group showing 0.300 kg and the fennel group showing 0.330 kg. The MDA, SOD, protein, and catalase values were examined in the collected blood samples, revealing significant differences in MDA, SOD, and catalase values, while no significant difference was observed in PCO values. The addition of fennel seeds showed an increase in antioxidant levels and a decrease in lipid peroxidation, which could effectively protect rams from oxidative stress that reduces their productivity and resilience. Moreover, the study concluded that the use of fennel seeds in ram rations did not have any harmful effects.